Pengelolaan Persediaan Ikan Tuna Di PT. Tuna Mantap - Febriani, Febriani; Tuli, Hartati; Husain, Siti Pratiwi (Jurnal Mirai Management, 2024)
Study This aim For know How planning, implementation and control as well as role EOQ method in efficiency cost supply company. This research uses a qualitative method with a descriptive approach using primary data sources obtained directly from observations and interviews as well as documentation data. Study This carried out by the author at PT. Tuna Mantap located inside place fish auction. Results obtained that PT. Tuna Steady Already do planning However Not yet effective and efficient, as well implementation and control in count Still Not yet use method and only use estimation just. with use method economic order quantity (EOQ) control helps company determine how much economical every item inventory and know frequency booking For something period as well as When booking goods must repeated, so request can fulfilled in a way maximum. With Thus, the economic order quantity (EOQ) method has role important in arrange efficiency inside costs company. Key Words: Inventory, Planning, Economic Order Quantity (EOQ) Method